2018
DOI: 10.2152/jmi.65.126
|View full text |Cite
|
Sign up to set email alerts
|

High defect stage, contralateral defects, and poor flexibility are negative predictive factors of bone union in pediatric and adolescent athletes with spondylolysis

Abstract: : Purpose : To identify predisposition to spondylolysis and physical characteristics associated with "bone union" following conservative spondylolysis treatment among pediatric and adolescent athletes. Methods : We retrospectively analyzed pediatric and adolescent athletes with spondylolysis who underwent conservative treatment and rehabilitation for three or more consecutive months following sports activity cessation. Patients with terminal spondylolysis or who did not discontinue sports activities were exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
(33 reference statements)
1
15
1
Order By: Relevance
“…In this study, we found that 15% of our 10 patients with lumbar spondylolysis were track and field athletes, followed by baseball and 11 soccer players. This finding was proportionally high compared with previous studies that 12 reported a 7%-11% prevalence of lumbar spondylolysis in track and field athletes 9,10) , 13 thus suggesting that movements required during running may be involved in the 14 pathogenetic mechanism of spondylolysis in track and field athletes. 15…”
Section: Dash-associated Spondylolysis Hypothesismentioning
confidence: 45%
See 1 more Smart Citation
“…In this study, we found that 15% of our 10 patients with lumbar spondylolysis were track and field athletes, followed by baseball and 11 soccer players. This finding was proportionally high compared with previous studies that 12 reported a 7%-11% prevalence of lumbar spondylolysis in track and field athletes 9,10) , 13 thus suggesting that movements required during running may be involved in the 14 pathogenetic mechanism of spondylolysis in track and field athletes. 15…”
Section: Dash-associated Spondylolysis Hypothesismentioning
confidence: 45%
“…10 During a soccer game, maximal-and high-intensity sprints (Dash) by players are mixed 11 with moderate-and low-intensity running (Jog). In the 2014 World Cup, the mean number 12 of sprints per player in a soccer game was 33.25 ± 10.67 6) .…”
Section: Introductionmentioning
confidence: 99%
“…6 in our study, the bone union rate and the treatment period did not differ so much between adolescents and adults. In a previous study 16) , patients with bilateral acute spondylolysis were excluded, and some patients exhibited pseudarthrosis lesions on the contralateral side, which negatively impacts bone union [17][18][19] ; these factors prevent simple comparisons between these studies. Nonetheless, for adult-onset acute spondylolysis with bone edema, conservative therapy is probably as effective as during adolescence with regard to achievement of bone union.…”
Section: Discussionmentioning
confidence: 99%
“…Where bone healing was achieved with conservative treatment, Yamazaki et al [ 6 ] reported that bone healing rates where the contralateral side was progressive-stage and terminal-stage were 16.9% and 3.4%, respectively. Fujii et al [ 8 ] reported that the bone healing rate without contralateral defects or with contralateral early-stage spondylolysis was significantly higher than that for those with contralateral progressive or terminal-stage spondylolysis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that this process progresses to lumbar spondylolisthesis, where a vertebra slips from its location to rest on the lower bone. There have been some reports that the pathological stage on the contralateral side can affect bone healing [6][7][8], but no reports have exclusively examined L5 spondylolysis.…”
Section: Introductionmentioning
confidence: 99%